Development of Electronic LKPD to Support PJBL Environmental Change Materials to Improve Creative Thinking Skills and Environmental Literacy of Phase E Students in Independent Learning - Agustin, Arumi; Tias Pratama , Anggi (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to determine the feasibility, practicality, and effectiveness of Electronic LKPD Supporting on PjBL on in improving creative thinking skills and environmental literacy of students at SMAN 1 Tarakan. This type of research is research and development (Research and Development) with the ADDIE model (analyze, design, development, implement, evaluate). The analyze stage includes initial analysis, competency analysis, constructional analysis, and content analysis. The design stage includes compiling an electronic LKPD outline and designing learning content in the LKPD. The development stage includes developing data collection instruments. The data collection instruments in this study were a feasibility sheet for expert lecturers, a practicality sheet for biology teachers, a student readability sheet, and pretest and posttest questions for creative thinking skills and environmental literacy. This instrument was developed based on the review of the supervisor, assessment of expert lecturers, biology teachers, and trials on students. The implement stage includes the application of electronic LKPD that has been developed on class X students of SMAN 1 Tarakan. The experimental design used is the pretest-posttest control group design. The evaluate stage includes the form of evaluation carried out at each stage of ADDIE. The data analysis technique uses the manova test. The results of the study show: (1) The electronic LKPD supporting PjBL that was developed meets the criteria of being very valid for use in learning activities with an average value according to media experts of 3.55, material experts of 3.89 and learning experts of 3.96. (2) Practicality with a very practical category for use based on the results of student and teacher responses. (3) Effectiveness based on the Multivariate Analysis of Variance test with a significance level of 5% shows that there is an influence on students' creative thinking skills and environmental literacy after treatment using electronic LKPD supporting PjBL.